Human capital and income inequality - Jong-Wha Lee; Hanol Lee (Asian Development Bank Institute (ADBI), 2018)
This study investigates empirically how human capital, measured by educational attainment, is related to income distribution. The regressions, using a panel data set covering a broad range of countries between 1980 and 2015, show that a more equal distribution of education contributes significantly to reducing income inequality. Educational expansion is a major factor in reducing educational inequality and thus income inequality. Public policies that improve social benefits and price stability contribute to reducing income inequality, while public spending on education helps to reduce educational inequality. In contrast, higher per capita income, greater openness to international trade, and faster technological progress tend to make both income and education distribution more unequal. Using the calibration of empirical results, we find that we can attribute the rising income inequality within East Asian economies in recent decades to the unequalizing effects of fast income growth and rapid progress in globalization and technological change, which have surpassed the income-equalizing effects from improved equality in the distribution of educational attainment during the period.
Keywords: D31; H52; I24; O53; 330; income distribution; inequality; human capital; education; globalization; technological change